Dietary Fibers (Gum Arabic) Supplementation Modulates Hepatic and Renal Profile Among Rheumatoid Arthritis Patients, Phase II Trial - Kamal, Ebtihal; Kaddam, Lamis AbdelGadir; Alagib, Alnour; Saeed, Amal (Frontiers in Nutrition, 2021)
Background: Rheumatoid arthritis (RA) is an autoimmune disease that mainly affects the synovial joints with systemic manifestations. RA has a major impact on liver and kidney functions as part of disease pathogenesis or as a sequel of disease medications, or mostly both of them. The kidney and liver involvement increases the RA morbidity and mortality. Nowadays, dietary interventions are proposed as potential modifiers for disease severity. Gum Arabic (GA) is Achaia Senegal exudates; it is soluble fibers with prebiotic properties. GA discovered to be protective against experimental nephrotoxicity and hepatotoxicity, with comparable findings among human studies. This article addresses the effect of GA on hepatic and renal profile among RA patients Methods: Forty patients aged 18 to 70 received GA daily for twelve weeks as 30 grams single dose. The liver enzymes, total protein level, serum albumin, serum globulin level, urea, creatinine, and serum electrolytes have been measured as a baseline after 4 weeks and by the end of the study. Cobas C311 (Roche, Germany) automated chemistry analyzer directly determined the values for total protein, albumin, alaninamino transferase(ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and creatinine. The study ethically has been approved by the Ethical Committee of the National Medicines and Poisons Board. Trial Registration Identifier: NCT02804581. Results: Regarding the liver enzymes, GA has significantly decreased the liver enzymes apart from alkaline phosphatase, which showed no significant change. In contrast, GA has increased the serum albumin level with a minor impact on the serum globulin level. Furthermore, GA has also significantly decreased the level of urea (P. value: 0.0001) and level of Sodium (P. value: 0.002) with insignificant change on creatinine and potassium concentrations. Conclusion: GA reveals hepatic and renal protective effects among RA patients, evidenced by the significant reduction of urea and liver enzymes. Thus it can be recommended as a dietary supplement for RA patients. Though, we recommend more investigations to support our findings.